Makna Kepemimpinan Daud dalam Perjanjian Lama - Steven Tubagus (KINAA: Jurnal Kepemimpinan Kristen dan Pemberdayaan Jemaat, 2020)
Abstract. The leadership crisis is felt based on a lack of trust in leaders. Based on this, leadership contributions from the Scriptures need to be contributed—the Meaning of David's Leadership in the Old Testament. The purpose of this paper is to describe the meaning of David's leadership, according to the Old Testament textually. The method used is qualitative, using the study of literature that is the Bible and reference books. The results of the study are that David's Leadership is an example and role model for everyone because it leads people to believe in God so that their goals are achieved. The meaning of David's leadership in the old covenant is: first, leadership that pleases God and knowing God's will. Second, David's Unchanging Leadership.  Third, Attitudes towards God: wholeheartedly cling to Him. Fourth, leaders who can be accountable for all decisions.   Keywords: Meaning, David, Leadership, Old Testament.   Abstrak: Krisis kepemimpinan dirasakan berdasarkan kurangnya kepercayan kepada pemimpin. Berdasarkan hal tersebut perlu sumbangsih kepempimpinan dari Kitab Suci. Makna Kepemimpinan Daud dalam Perjanjian Lama. Tujuan dari tulisan ini adalah untuk mendeksripsikan makna kepemipinan Daud menurut Perjanjian lama secara tekstual. Metode yang digunakan kualitatif, dengan memakai studi literatur yaitu Alkitab dan buku-buku refrensi. Hasil penelitian yaitu Kepemimpinan Daud menjadi contoh dan teladan untuk semua orang karena membawa orang-orang untuk percaya kepada Allah sehingga tujuannya tercapai. Makna kepemimpinan Daud dalam perjanjian lama yaitu: pertama, Kepemimpinan yang berkenan kepada Allah yaitu mengetahui kehendak Allah. Kedua, Kepemimpinan Daud Yang Tidak Berubah. Ketiga, Sikap terhadap Allah: sepenuh Hati berpaut kepada-Nya. Keempat, Pemimpin yang dapat mempertanggungjawabkan semua keputusannya.